HEXAGON FRAUD IN FRAUDULENT FINANCIAL STATEMENT: PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Muhthadin, Mohammad Al; Amin, Muhammad Nuryatno (Jurnal Aplikasi Akuntansi, 2023)
The study aims to shed light on the role of hexagon fraud elements in presenting misleading financial data by companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021. Purposive sampling was employed to compile information from 82 companies for this research. This study makes use of logistic regression analysis. Financial statement fraud was found to be influenced solely by arrogance as opposed to factors such as external pressure, director change, effective monitoring, rationalization, or conspiracy. Based on agency theory, it can explain how fraudulent financial statements occur so that companies and investors can be prevented later.